OSBPL3 promotes colorectal cancer progression through modulation of TGF-β signaling and immune cell infiltration - Liang, Weijun; Wang, Chengxing; Wei, Jianchang; Zhou, Chaorong; He, Canxiu; He, Yaoming; Zhao, Jinglin; Li, Shangren; Cao, Jie (Translational Cancer Research, 2026)
Colorectal cancer (CRC) is the third most common cancer worldwide, with prognosis often limited by disease progression. The role of oxysterol-binding protein-like 3 (OSBPL3) in various cancers remains unclear. This study aimed to investigate the expression, biological function, and relationship of OSBPL3 with the tumor microenvironment (TME) in CRC, and to assess its potential as a therapeutic target.